General practice for the poor and specialist services for the rich: inequality evidence from a cross-sectional survey on Hangzhou residents, China - Tao Zhang; Chaojie Liu; Lingrui Liu; Yong Gan; Wei Lu; Hongbing Tao (BMC, 2019)
Abstract Background Inequalities in health care services are becoming an increasing concern in the world including in China. This study measured the income-related inequalities of residents in Hangzhou of China in access to general practice and specialist care and identified socioeconomic factors associated with such inequalities. Methods A cross-sectional questionnaire survey was conducted on 1048 residents in ten urban communities in Hangzhou, China. The percentage and frequency of respondents visiting general practice (GP) and hospital specialist clinics over the past four weeks prior to the survey were estimated. Income-related inequalities in access to these services were measured by the concentration index. Logistic regression and Poisson regression models were established to decompose the contributions of socioeconomic factors (residency, income, education, marital status, and social health insurance) to the inequalities in the probability and frequency of accessing these services, respectively, after adjustment for the needs factors (age, sex and illness conditions). Results The GP services were in favor of the poor, with a concentration index of − 0.0464 and − 0.1346 for the probability and frequency of GP visits, respectively. In contrast, the specialist services were in favor of the rich, with a concentration index of 0.1258 and 0.1279 for the probability and frequency of specialist visits, respectively. Income is the biggest contributor to the inequalities, except for the frequency of visits to specialists in which education played the greatest role. Conclusions Income-related inequalities in GP and specialist care are evident in China. Policy interventions should pay increasing attention to the emergence of a two-tier system, potentially enlarging socioeconomic disparities in health care services.